Práticas e condições organizacionais relacionadas à gestão do conhecimento: um estudo de caso na Samarco Mineração S/A. - Esther Leopoldo Lage (2003)
This dissertation aimed at studying the organizational practices and the infrastructure related to the knowledge management, through a case study of a Brazilian company belonging to the mineral sector, named Samarco Minerações S.A. The motivation of this study was to analyzeacademic / theoretical considerations and the practical reality of knowledge management within a company. It is a qualitative study with a descriptive feature, which was accomplished by means of interviews, observations and documental analyses. The work intended tounderstand what kind of infrastructure is offered by the company in order to support knowledge management in terms of culture, technology and structure. It also analyzed practices used by the company to create, acquire, convert, use and protect its knowledge. The main conclusions were that knowledge is the basis of both competitive advantage and ability to adapt / innovate considering internal and external challenges. People are the center of knowledge management, and they need to be motivated, prepared and committed to the process so that it can happen. Finally, organizational changes are extremely relevant to promote and facilitate creation, acquisition, conversion, use and protection of knowledge in order to convert it into a competitive resource for the company.